E-Commerce (Marketplace) untuk Pemasaran Produk UMKM di Kelurahan Balekambang–Jakarta Timur (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2021)
The problems faced by the Balekambang community UMKM are conventional marketing, sales based on sales and cash. Balekambang community MSMEs have not yet utilized e-commerce technology as a means of marketing products. As a result, the marketing area is very limited (local). So that the purpose of holding this PKM is expected that 80% of Community Service participants are able to plan product marketing and have e-commerce-based application management skills (for example: website, Market Place, Instagram, Facebook, Twitter, etc.) for marketing UMKM products in Balekambang-East Jakarta. This method of implementing Community Service (PKM) is in the form of a Website & Marketplace Workshop for the Balekambang Community-East Jakarta already has a business that has been running for at least 3-6 months and has the intention of opening a business (new entrepreneurship). As a partner in this PKM activity, the Karang Taruna manager provides supporting infrastructure for community service activities such as providing PKM space, sound system, focus, blackboard, chairs and tables, etc. The results of this PKM activity partners want to actively participate in every activity held. The partner succeeded in applying directly from the theory obtained at the previous PKM meeting to improve product quality and increase its market share in the future, in the form of having a sales account and making transactions to generate income in one of the serving market places. as a PKM training medium.